Simple 3-D Stimulus for Motion Parallax and its Simulation. (May 2013) - Ono, Hiroshi; Chornenkyy, Yevgen; D'Amour, Sarah
Simulation of a given stimulus situation should produce the same perception as the original. Rogers et al (2009 Perception 38 907–911) simulated Wheeler's (1982, PhD thesis, Rutgers University, NJ) motion parallax stimulus and obtained quite different perceptions. Wheeler's observers were unable to reliably report the correct direction of depth, whereas Rogers's were. With three experiments we explored the possible reasons for the discrepancy. Our results suggest that Rogers was able to see depth from the simulation partly due to his experience seeing depth with random dot surfaces.